Resilience and sustainability of entrepreneurial mindsets in Ghanaian youth: a five-year impact study of sports training programs - Oscar Cornelius Nyanyo Nyanyofio; Karim Musah; Vida Korleki Nyawornota; Doris Akosua Tay; Clement Adamba; Leapetswe Malete; Daniel McCole; Reginald Tetteh-Ahumah Ocansey; Reginald Tetteh-Ahumah Ocansey (Frontiers in Education)
IntroductionYouth sports programs are recognized as effective tools for fostering entrepreneurial mindsets, resilience, and sustainable personal development. This study evaluates the long-term impact of the Africa Alliance for Partnerships (AAP) program on the academic and professional trajectories of its alumni, with a focus on sustained entrepreneurial skills and personal growth.MethodsA structured survey was conducted among alumni who participated in the AAP program at least five years prior. Data on academic performance, career development, entrepreneurial activities, and personal experiences were collected and analyzed. Quantitative data were subjected to statistical tests, including regression and correlation analyses, while qualitative feedback underwent sentiment analysis.ResultsFindings indicate significant academic performance improvements and enhanced entrepreneurial skills among participants. The average skill application scores increased consistently from 2018 to 2023, with a strong positive correlation (r = 0.75) between skill application and academic improvement. Sentiment analysis revealed predominantly positive feedback, underscoring participant satisfaction with the program. Gender analysis showed no significant differences in outcomes, highlighting the program’s inclusivity.DiscussionThe AAP program successfully instilled entrepreneurial mindsets and resilience, sustained over five years. Key factors contributing to its success include mentorship, leadership training, and exposure to real-world challenges. These findings demonstrate the potential of sports-based youth development programs as sustainable models for fostering entrepreneurship and personal growth. Future research should explore additional external factors influencing outcomes and assess the scalability of such programs in diverse contexts.